Organizational Financial Performance and Entrepreneurial Intentions Among Employed Persons - Mali, Predrag; Mitić, Siniša; Kuzmanović, Bogdan; Nikolić, Milan (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
The paper presents the results of the study of the influence of the organizational financial performance on individual entrepreneurial orientation dimensions, achievement dimension and the theory of planned behaviour dimensions, among employed persons. Respondents were employed persons in organizations in Serbia. The final sample consists of 540 respondents from 72 companies. Of the financial performance items, Market share, then Sales growth and Asset growth have the strongest impact on the individual entrepreneurial orientation dimensions, achievement dimension and the theory of planned behavior dimensions. The weakest influence has the Salaries item: the perceived salary level has no significant effect on the observed dimensions. However, regression analysis showed that the Salaries item has a statistically significant and negative predictive effect on the dimension Subjective norm. The theoretical significance of this research is that very few papers address entrepreneurial intentions among employed persons. The practical significance of the paper is that it shows that employed persons should definitely be counted as potential entrepreneurs.